Die Wiener Niederleger um 1700 - Peter Rauscher; Andrea Serles (Österreichische Zeitschrift für Geschichtswissenschaften, 2015)
In 1515, a group of German, later also Swiss and Italian or Savoyard merchants received permission to settle in Vienna and to deal wholesale during the entire year. These so-called „warehousers“ kept their status of being foreign, mostly protestant, inhabitants of the Habsburg capital for almost three centuries. During the early modern period, the warehousers dominated the Viennese wholesale trade, participated in the early establishment of factories from the late 17th century onwards and acted as Imperial creditors. Even if the warehousers are often mentioned in studies on Viennese and Austrian social and economic history, their commercial activities, business contacts and also family relationships are hardly known. As a pilot study, this article offers a broad overview of the current state of research and the most important primary sources. It discusses the wider context of the warehousers’ business activities (the development of the Austrian lands, Imperial commercial policy, markets in Upper and Lower Austria, and consumption in Vienna and its hinterland). The last chapter of the article provides an introduction to some prominent warehouser companies in the age of mercantilism and offers the earliest complete survey of all warehousers drawing on a list from the year 1725.